2016
DOI: 10.1002/2015jg003050
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive multiyear carbon budget of a temperate headwater stream

Abstract: Headwater streams comprise nearly 90% of the total length of perennial channels in global catchments. They mineralize organic carbon entering from terrestrial systems, evade terrestrial carbon dioxide (CO2), and generate and remove carbon through in‐stream primary production and respiration. Despite their importance, headwater streams are often neglected in global carbon budgets primarily because of a lack of available data. We measured these processes, in detail, over a 10 year period in a stream draining a 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 49 publications
5
31
1
Order By: Relevance
“…Instead, we argue the long-term integration of the nitrogen, carbon, and phosphorous cycles in the system appears to be at approximately steady-state under the diel hydrologic forcing of flows in the stream. This interpretation is consistent with past studies in the same watershed, which concluded that biological limitations are the primary control on nutrient cycling during low flows [115].…”
Section: Rru Production Does Not Appear To Change With Dischargesupporting
confidence: 93%
“…Instead, we argue the long-term integration of the nitrogen, carbon, and phosphorous cycles in the system appears to be at approximately steady-state under the diel hydrologic forcing of flows in the stream. This interpretation is consistent with past studies in the same watershed, which concluded that biological limitations are the primary control on nutrient cycling during low flows [115].…”
Section: Rru Production Does Not Appear To Change With Dischargesupporting
confidence: 93%
“…Second, hyporheic exchange provides a mechanism to transport CO 2 from the floodplain to the stream where it can be evaded to the atmosphere or transported downstream. Estimates for WS1 suggest that these hyporheic processes account for 24% of the carbon exported from the watershed [ Argerich et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…For hyporheic systems that are subject to episodic nutrient replenishment (e.g., autumnal leaf fall), one would expect that nutrient levels (primarily organic carbon) would change over time, decreasing between replenishment events. Several studies have demonstrated a positive relationship between nutrient concentrations and bioactivity levels (e.g., Argerich et al, ; Harvey et al, ; Hunter et al, ; Sobczak & Findlay, ; Suberkropp, ; Zarnetske et al, ). This idea has also been presented, at least as a theoretical construct, in a number of numerical studies (see e.g., Bardini et al, ; Kessler et al, ; Marzadri et al, ; Rutherford et al, ; Wriedt & Rode, ; Zarnetske et al, ).…”
Section: Introductionmentioning
confidence: 99%